Review Artikel: Pengaruh Penggunaan Bahan Pengikat Alami dan Sintetis pada Kualitas Fisik Tablet - Siti Nurhaliza; Nur Luthfia Salim; Annisa Normiani Putri; Lidya Syahjiah; Muhammad Dhaiffullah; Nor Latifah (An-Najat, 2024)
Tablets are one of the most preferred forms of medication due to their compact shape, portability, and good stability. A key factor that greatly influences the physical quality of tablets is the binder used. This article reviews various studies on the effects of using natural and synthetic binders on the physical quality of tablets in drug formulations, including PVC, HPMC, CMC-Na, jackfruit seed starch, banana heart starch, and white sweet potato starch, which contribute to forming tablets with optimal physical properties. Data on the use of tablet binders were collected through a literature study method. The results concluded that the use of PVC, HPMC, CMC-Na, jackfruit seed starch, banana heart starch, and white sweet potato starch binders have an impact on the physical properties of tablets.